Post-Variscan evolution of the Anti-Atlas belt of Morocco constrained from low-temperature geochronology - Gouiza, M.; Charton, R.; Bertotti, G.; Andriessen, P.; Storms, J. E. A. (International journal of earth sciences : Geologische Rundschau, 2017)
The Anti-Atlas belt of Morocco extends ENE–WSW, over more than 600 km, from the Atlantic margin in the west to the interior of the African plate in the east. It exhibits Precambrian rocks outcropping as basement inliers and surrounded by marine Ediacaran–Cambrian sequences around the axis of the mountain range. The belt, which has for a long time been interpreted as of Variscan age, is now revealed to have experienced major vertical movements through Mesozoic and Cenozoic times. Thereby, the Anti-Atlas domain appears to be affected by two episodes of exhumation separated by an episode of subsidence. The initial episode occurred in the Late Triassic and led to the exhumation of 7.5–10.5 km of crustal rocks by the end of the Middle Jurassic (ca. 160–150 Ma). The following phase resulted in 1–3 km of basement subsidence and occurred during the Late Jurassic and most of the Early Cretaceous. The basement rocks were then slowly brought to the surface after experiencing 2–3.5 km of exhumation throughout the Late Cretaceous and the Cenozoic. The timing of these episodes of exhumation and subsidence coincides with major tectonic and thermal events in relation with the evolution of the Atlantic and Tethys Oceans, indicating that the effects of their rifting and drifting extended beyond their presumed margins.